2010
DOI: 10.4315/0362-028x-73.7.1219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Enterotoxin Production and Phenotypic Characteristics between Emetic and Enterotoxic Bacillus cereus

Abstract: Bacillus cereus was divided into emetic toxin (cereulide)- and enterotoxin-producing strains, but emetic toxin-producing B. cereus is difficult to detect immunochemically. Screening methods for emetic toxin-producing B. cereus are needed. The objectives of this study were to identify and detect emetic toxin-producing B. cereus among 160 B. cereus strains, and to compare enterotoxin production and phenotypic characteristics between the emetic toxin-producing and enterotoxin-producing strains. Forty emetic toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
9
19
0
Order By: Relevance
“…The percentage of isolates carrying nheABC in this study is in good agreement with previous studies (Anderson et al, 2001;Kim et al, 2010a;Lee et al, 2012), which demonstrated that 90-100% of the emetic and nonemetic isolates possessed these genes. Guinebretière et al (2002) also showed that almost all the strains from food poisoning and foodborne ecosystems harbored the nhe genes.…”
Section: Enterotoxin Production and Profiling Of Related Genessupporting
confidence: 93%
See 2 more Smart Citations
“…The percentage of isolates carrying nheABC in this study is in good agreement with previous studies (Anderson et al, 2001;Kim et al, 2010a;Lee et al, 2012), which demonstrated that 90-100% of the emetic and nonemetic isolates possessed these genes. Guinebretière et al (2002) also showed that almost all the strains from food poisoning and foodborne ecosystems harbored the nhe genes.…”
Section: Enterotoxin Production and Profiling Of Related Genessupporting
confidence: 93%
“…This is consistent with previous results identifying the cytK gene among emetic isolates as ranging from 12.1% to 27.5% (Ehling-Schulz et al, 2005a;Kim et al, 2010a). Granum et al (1996) reported that bceT was present in two of the seven food-poisoning B. cereus isolates.…”
Section: Enterotoxin Production and Profiling Of Related Genessupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, some emetic strains producing NHE were found to be very cytotoxic for Caco-2 cells, as previously reported (14). Furthermore, the simultaneous presence of the genetic determinants for cereulide and the genes encoding potential enterotoxins was recently demonstrated for a B. cereus strain (19,20), which appeared to be particularly virulent. Could this fact have played a role in the necrosis of the colon, even though the cytK PCR was negative, since that this toxin is the one that has been implicated in necrotic enteritis (21)?…”
Section: Case Reportsupporting
confidence: 69%
“…B. cereus is famous for being implicated in foodborne disease (Griffiths and Schraft, 2017). B. cereus is accountable for 2 kinds of foodborne illness: the emetic and diarrheal syndromes (Kim et al, 2010). Severe attack of nausea and vomiting within 5 h after having the meal containing performed toxin (cereulid) is the characteristic feature of the emetic syndrome.…”
Section: Introductionmentioning
confidence: 99%